1981
DOI: 10.1111/j.1744-7348.1981.tb00750.x
|View full text |Cite
|
Sign up to set email alerts
|

Duration of cereal aphid populations and the effects on wheat yield and breadmaking quality

Abstract: SUMMARYField‐caged and open‐plot populations of the aphid Sitobion avenae on winter wheat (cv. Maris Widgeon) were sampled approximately twice‐weekly in the summer of 1978. Cage populations began at growth stage 10.2 (Feekes scale) (Zadoks, G. S. 52); they were removed by spraying with pirimicarb at growth stages 10.54 (71), 11.1–11.2 (77) and 11.2–11.3 (85) respectively. All cage populations reduced mean weight per grain but the effect per aphid unit was lowest in the population of longest duration. Although … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 10 publications
1
29
0
Order By: Relevance
“…Significant yield decrease occurred when the abundance of S avenae reached 20–30 aphids per plant during milk development 29. Lee et al 29 demonstrated that S avenae infestation affected not only yield quantity but the bread‐making quality of flour as well: colour, nicotinic acid content and thiamine content increased and the HMW glutenin content decreased.…”
Section: Discussionmentioning
confidence: 99%
“…Significant yield decrease occurred when the abundance of S avenae reached 20–30 aphids per plant during milk development 29. Lee et al 29 demonstrated that S avenae infestation affected not only yield quantity but the bread‐making quality of flour as well: colour, nicotinic acid content and thiamine content increased and the HMW glutenin content decreased.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies have indicated that the aphid reduces not only yields but also quality of injured grains (George & Gair, 1979;Lee et al, 1981;Malachowska, 1987). Earlier studies have indicated that the aphid reduces not only yields but also quality of injured grains (George & Gair, 1979;Lee et al, 1981;Malachowska, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…Sitobion avenae (Fabricius) infestation affects not only yield but also the bread‐making quality of flour (colour, increased nicotinic acid and thiamine content and decreased high‐molecular‐weight glutenin content) 10…”
Section: Introductionmentioning
confidence: 99%